Yield gap analysis and economics of onion (Allium cepa L.) cultivation in western Arid Kachchh of Gujarat (Indian Journal of Arid Horticulture, 2025)
Thirty-seven demonstrations on onion cultivation were executed to assess the  impact of improved farming practices on yield outcomes. Results indicated that  onions grown under the enhanced agricultural practices produced yields ranging  from 254.62 to 275.50 q/ha, significantly surpassing the yields under traditional  farmer practices, which varied from 205 to 216 q/ha. The yield increase under the  improved practices ranged from 24.20% to 27.55%. Economic assessments revealed  that the benefit-cost ratio in demonstration plots varied from 2.23 to 4.26, compared  to 2.02 to 3.80 in farmer-managed plots. The study emphasizes that adopting these  improved practices not only increases onion yield but also enhances the profitability  of onion farming.
Keywords: Adoption; bulb; exchange; foreign; FLDs; net return; onion; yield